2011
DOI: 10.1152/jn.01105.2010
|View full text |Cite
|
Sign up to set email alerts
|

Gastric and pyloric motor pattern control by a modulatory projection neuron in the intact crabCancer pagurus

Abstract: Hedrich UB, Diehl F, Stein W. Gastric and pyloric motor pattern control by a modulatory projection neuron in the intact crab Cancer pagurus. J Neurophysiol 105: 1671-1680, 2011. First published February 16, 2011 doi:10.1152/jn.01105.2010.-Neuronal release of modulatory substances provides motor pattern generating circuits with a high degree of flexibility. In vitro studies have characterized the actions of modulatory projection neurons in great detail in the stomatogastric nervous system, a model system for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 60 publications
(103 reference statements)
0
48
1
Order By: Relevance
“…We found that in unfed animals, the phase relationships of the pyloric neurons rarely deviated from the canonical patterns, indicating that the pyloric rhythm's structure remains stable. This was despite several studies showing that, in vivo, the STG is continuously exposed to both hormonal and neural modulation (Diehl et al, 2013;Hedrich et al, 2011;Behrens et al, 2008;Schmerberg and Li, 2013;Christie et al, 1995), which have the potential to modify the phase relationships of the involved motor neurons (Marder and Weimann, 1992).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We found that in unfed animals, the phase relationships of the pyloric neurons rarely deviated from the canonical patterns, indicating that the pyloric rhythm's structure remains stable. This was despite several studies showing that, in vivo, the STG is continuously exposed to both hormonal and neural modulation (Diehl et al, 2013;Hedrich et al, 2011;Behrens et al, 2008;Schmerberg and Li, 2013;Christie et al, 1995), which have the potential to modify the phase relationships of the involved motor neurons (Marder and Weimann, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, STG activity should be modulated by neuronal modulation as well as hormonal modulation. Curiously, however, despite stimulation of descending projection neurons both in vitro (Nusbaum and Beenhakker, 2002) and in vivo (Diehl et al, 2013;Hedrich et al, 2011) resulting in clear changes of CPG activity, most reported in vivo data show only the canonical motor patterns typically observed in unperturbed in vitro preparations (Hedrich et al, 2011;Massabuau and Meyrand, 1996;Clemens et al, 1998b). This is in spite of there being clear changes in the STG motor output in vitro Marder and Calabrese, 1996) and in vivo (Heinzel, 1988) in response to application of modulators known to be present in the blood (Li et al, 2002;Chen et al, 2009).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The single firing rate (10 Hz=100 ms inter-spike interval) and burst duration (4.8 s) used were also within the physiological range of LG activity (inter-spike interval: 50-250 ms; burst duration: 2-9 s) (Beenhakker et al, 2004(Beenhakker et al, , 2005(Beenhakker et al, , 2007Blitz et al, 2004bBlitz et al, , 2008Colton and Nusbaum, 2014;DeLong and Nusbaum, 2010;Diehl et al, 2013;Hedrich et al, 2011;Kirby and Nusbaum, 2007;White and Nusbaum, 2011). Thus, our data indicate that during gastric mill rhythms triggered by multiple inputs, augmentation and facilitation/ depression would regulate responses of the three target muscles of LG.…”
Section: Physiological Activity Rangementioning
confidence: 99%
“…Diehl et al (2013) focused on distinctions in the pattern of spiking within LG bursts, but a number of other aspects of LG activity differ depending on modulatory state and the complement of inputs acting on LG. In response to a number of different modulatory inputs, LG activity consists of firing rates of 4-20 Hz (50-250 ms inter-spike intervals), burst durations of 2-8 s and interburst intervals of 2-24 s in vitro and in vivo (Beenhakker et al, 2004(Beenhakker et al, , 2005(Beenhakker et al, , 2007Blitz et al, 2004bBlitz et al, , 2008Colton and Nusbaum, 2014;DeLong and Nusbaum, 2010;Diehl et al, 2013;Hedrich et al, 2011;Kirby and Nusbaum, 2007;White and Nusbaum, 2011). Similar to central and peripheral synapses in other systems, electrical responses at neuromuscular junctions in the STNS are shaped by multiple forms of activity-dependent synaptic plasticity including depression, facilitation and augmentation (Daur et al, 2012b;Jorge-Rivera et al, 1998;Katz et al, 1993;Sen et al, 1996;Stein et al, 2006).…”
Section: Introductionmentioning
confidence: 99%